A coming of age: how and why the UK became the first democracy to allow votes for 18-year-olds. Issue 2 (3rd April 2021) - Loughran, Thomas; Mycock, Andrew; Tonge, Jonathan
ABSTRACT: In 1969, the UK became the first country to lower its age of franchise to 18. Most other democracies soon followed. This article provides the first detailed examination of the debates and processes which contributed to the UK's pioneering reform of the age of enfranchisement. It explores parliamentary and press debates during the 1960s, arguing that lowering the voting age to 18 was not in response to popular mobilisation by the public or pressure groups, nor the outcome of significant political contestation. Rather, voting age reform was a consequence of the desire of political leaders to align the voting age with what society increasingly perceived as the new age of adulthood, 18. Lowering the voting age was part of package of reforms which attempted to streamline the age at which young people were seen to become adults.